2008
DOI: 10.1038/nchembio.106
|View full text |Cite
|
Sign up to set email alerts
|

Cytosporone B is an agonist for nuclear orphan receptor Nur77

Abstract: Nuclear orphan receptor Nur77 has important roles in many biological processes. However, a physiological ligand for Nur77 has not been identified. Here, we report that the octaketide cytosporone B (Csn-B) is a naturally occurring agonist for Nur77. Csn-B specifically binds to the ligand-binding domain of Nur77 and stimulates Nur77-dependent transactivational activity towards target genes including Nr4a1 (Nur77) itself, which contains multiple consensus response elements allowing positive autoregulation in a Cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
321
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(334 citation statements)
references
References 41 publications
11
321
2
Order By: Relevance
“…Moreover, this finding is supported by two recent studies where NR4A1 was found to be down-regulated in FC (Fryknas et al 2006, Camacho et al 2009). NR4A1 and NR4A3 also known as Nur77 and Nor-1 respectively are homologous orphan nuclear receptors that regulate the transcription of a common set of target genes (Li et al 2006), and both have been described as homeostatic regulators of proliferation and apoptosis (Moll et al 2006, Zhan et al 2008. While NR4A1-and NR4A3-deficient mice respectively exhibit subtle phenotypes, it was recently shown that double knockout quickly leads to acute myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this finding is supported by two recent studies where NR4A1 was found to be down-regulated in FC (Fryknas et al 2006, Camacho et al 2009). NR4A1 and NR4A3 also known as Nur77 and Nor-1 respectively are homologous orphan nuclear receptors that regulate the transcription of a common set of target genes (Li et al 2006), and both have been described as homeostatic regulators of proliferation and apoptosis (Moll et al 2006, Zhan et al 2008. While NR4A1-and NR4A3-deficient mice respectively exhibit subtle phenotypes, it was recently shown that double knockout quickly leads to acute myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…1 Some of them display antibacterial activity. [1][2][3] Particularly, a recent excellent report by Wu et al 4 has revealed that Cytosporone B acted as an agonist for Nur77. Nuclear receptors play important roles in numerous biological processes such as cell proliferation, differentiation, apoptosis, metabolism and development.…”
Section: Introductionmentioning
confidence: 99%
“…These results reveal that Cytosporone B may be useful in the development of new therapeutic drugs to treat cancer and hypoglycemia. 4 The novel structures of Cytosporone B combining with remarkable biological activity and lack of availability from natural sources have attracted interest from chemists for its total synthesis. In the following we report on the total synthesis of this compound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…May be activated by DY131 Nur77 NR4A1 Nerve growth factor IB, NGFI-B, NAK1, ST59, TR3, HMR ENSG00000123358 An exogenous agonist, cytosporone B, has been described (Zhan et al, 2008), although structural analysis and molecular modelling has not identified a ligand binding site (Baker et al, 2003;Flaig et al, 2005; Liver X and farnesoid X Overview: Liver X and farnesoid X receptors (LXR and FXR, nomenclature as agreed by NC-IUPHAR Committee on Nuclear Receptors, see are members of a steroid analogue-activated nuclear receptor subfamily (ENSF00000000720), which form heterodimers with members of the retinoid X receptor family. Endogenous ligands for LXRs include hydroxycholesterols (OHC), while FXRs appear to be activated by bile acids.…”
Section: Ensg00000196482mentioning
confidence: 99%